THE INFLUENCE OF DIGITAL LITERACY AND FINANCIAL SELF EFFICACY ON RISKY CREDIT BEHAVIOR IN USING SHOPEE PAY LATER - Muhammad Rizky Yahya; Liestyowati Liestyowati; Jamaluddin Majid; Nurchayati Nurchayati; Listiana Sri Mulastih (ITB AAS Indonesia Surakarta, 2024)
Abstract Digital Literacy is an important instrument to strengthen customer strength to avoid risky credit behavior. Apart from Digital Literacy, Financial Self Efficacy is also an important instrument to avoid this. Therefore, this research aims to analyze the influence of digital literacy and financial self-efficacy on risky credit behavior. This research is quantitative research with an explantory approach, namely research that uses previous research as a stepping stone for finding new findings. The data used in this research uses primary data collected using the 1-5 questionnaire method which contains agree, strongly agree, disagree and strongly disagree. The data used was analyzed via PLS 3.0. The research results show that the Digital Literacy and Financial Self Efficacy variables each have a positive relationship and a significant influence on Risky Credit Behavior. As Digital Literacy improves and Confidence in managing finances increases, it will further strengthen the potential of employees to avoid Risky Credit Behavior.. Keywords : Digital Literacy, Financial Self Eficacy, Risky Credit Behavior